Cyclic voltammetry at microdroplet modified electrodes. A comparison of the reaction of vicinal dibromides with vitamin B-12s at the liquid/liquid interface with the corresponding homogeneous process: evidence for polar-solvent effects at the liquid/liquid interface - Davies, T; Garner, A; Davies, S; Compton, R (2004)
The electrocatalytic reactions of vitamin B12s with three vicinal dibromides (cis-1,2-dibromocyclohexane, trans-1,2-dibromocyclohexane and 1,2-dibromobutane) are investigated in homogeneous and heterogeneous media. In the latter, cyclic voltammetry with basal plane pyrolytic graphite electrodes modified with microdroplets of dodecane+dibromide is employed to obtain kinetic parameters for the liquid/liquid reaction. The homogeneous and interfacial reactions exhibit marked differences in reactivity and the contrasting behaviour of the two systems suggests the liquid/liquid interface has a major role in the B12s/RBr2 reaction, consistent with a polar solvent effect. © 2004 Elsevier B.V. All rights reserved.